DETEKSI DINI DAN EDUKASI BRAIN GYM SEBAGAI PENCEGAHAN DEMENSIA MELALUI PROGRAM PENGABDIAN DI POSYANDU WINONG - Anna Sarifah; Azka Arsyada Hafizha; Helmi Nugraheni; Soraya Ismi Nur Azizah; Tegar Pamungkas; Cahyo Setiawan; Alinda Nur Ramadhani (Jurnal Padamu Negeri, 2025)
Dementia is a disorder of cognitive function that results in disruption of daily activities and the quality of life of sufferers. In Boyolali Regency, the phenomenon of dementia is increasing along with the increase in the number of the elderly. However, public understanding of the symptoms and early treatment of dementia is still low. This Community Service Program aims to increase public knowledge and awareness of dementia through education, brain gym training, and early detection of dementia through the Clock Drawing Test (CDT). The activity was carried out at Posyandu Winong, Karangduwet Village with interactive lectures, joint discussions, and demonstrations. The results of the evaluation showed that there was an increase in participants' understanding of dementia from 24% in the pre-test to 80% in the post-test. Through this program, it shows that the participants gain important insights on the importance of maintaining cognition from an early age and doing physical activities such as Brain Gym regularly.